Genome-wide analysis of HSF family and overexpression of PsnHSF21 confers salt tolerance in Populus simonii × P. nigra - Guo, Qing; Wei, Ran; Xu, Min; Yao, Wenjing; Jiang, Jiahui; Ma, Xujun; Qu, Guanzheng; Jiang, Tingbo (Frontiers in Plant Science, 2023)
Heat shock transcription factor (HSF) is an important TF family that performs a dominant role in plant growing development and stress response network. In this study, we identified a total of 30 HSF members from poplar, which are unevenly distributed on 17 chromosomes. Poplar HSF family can be divided into three subfamilies and the members in the same subfamily share relatively conserved domains and motifs. HSF family members are acidic and hydrophilic proteins, locating in the nucleus, which mainly carry out gene expansion through segmental replication. In addition, they have rich collinearity across plant species. Based on RNA-Seq analysis, we explored the expression pattern of PtHSFs under salt stress. Subsequently, we cloned the significantly up-regulated PtHSF21 gene and transformed it into Populus simonii × P. nigra. The transgenic poplar over-expressing PtHSF21 had a better growth state and higher active oxygen scavenging ability under salt stress. Yeast one-hybrid experiment indicated PtHSF21 could improve salt tolerance by specifically binding to anti-stress cis-acting elements HSE. This study comprehensively profiled the fundamental information of poplar HSF family members and their responses to salt stress, and specifically validated the biological function of PtHSF21, which provides clues for further understanding the molecular mechanism of poplar HSF members in response salt stress.